Excited‐State Topology Modifications of the Dihydroazulene Photoswitch Through Aromaticity. Issue 8 (22nd July 2019) - Skov, Anders B.; Ree, Nicolai; Gertsen, Anders S.; Chabera, Pavel; Uhlig, Jens; Lissau, Jonas S.; Nucci, Luigi; Pullerits, Tõnu; Mikkelsen, Kurt V.; Brøndsted Nielsen, Mogens; Sølling, Theis I.; Hansen, Thorsten
Abstract: The front cover artwork is provided by the Hansen and Mikkelsen groups from the University of Copenhagen. The image shows how excited state aromaticity affects the photochemistry of dihydroazulene (DHA). Inducing aromaticity enhances an excited state barrier, so DHA can no longer reach the photoproduct. Read the full text of the Article at10.1002/cptc.201900088 . Abstract : "Gain and loss of aromaticity may be used as a driving force in solar energy storage when coupled to a photoswitch, such that a non‐aromatic photoisomer is formed by irradiation of an aromatic species. We find this to triple the energy storage in the dihydroazulene photoswitch, however we also find that the switching dynamics are drastically changed. We relate the changes in dynamics to the excited state aromaticity in the aromatic ring, which can be predicted computationally…" This and more about the story behind the front cover can be found in the Article at10.1002/cptc.201900088 .